Freeze the dynamicity: charge transfer complexation assisted control over the reaction pathway. Issue 43 (16th September 2019) - Singha, Nilotpal; Das, Basab Kanti; Pramanik, Bapan; Das, Saurav; Das, Debapratim
Abstract : Aqueous CT complexes of donor and acceptor molecules with reactive thiol groups were frozen and lyophilized to get alternate D–A assemblies in the solid state. Oxidation of the thiols resulted in asymmetric disulfides exclusively. Abstract : Charge transfer (CT) complexes between electron donor and acceptor molecules provide unique alternate D–A arrangements. However, these arrangements cannot be fully translated into chemo-selective organic transformations as the dynamicity of CT complexes in solution results in the co-existence of D–A assemblies and free monomers during the reaction time-scale. A conceptually new strategy to exploit CT complexes toward chemo-selective products by means of seizing the dynamicity of CT complexes is reported here. Aqueous CT complexes of donor and acceptor molecules bearing reactive thiol groups were frozen instantly and cryo-desiccated to get the alternate D–A assemblies intact in the solid state. Oxidation of reactive thiols in an oxygen rich solvent in the solid state resulted in the formation of the hetero-dimer exclusively. CT complexation and appropriate molecular arrangements are the key factors behind successful execution of this novel methodology. The strategy also paves the way to prepare unsymmetrical disulfide molecules from two dissimilar thiols.